(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article revolves around the importance and effectiveness of teaching English to children who are merely five years old. The article mainly discusses the psychological structure of children and the importance of using the ‘communicative method’ to teach English to children in early ages. Additionally, the importance of having a ‘positive emotional climate’ for the learner is discussed in the article. At the end of the article, the importance of teaching English to children who are merely five years old is highlighted by stating the benefits it would bring to the learner, such as cognitive development, correct pronunciation, and the ability to develop a good attitude for learning English.